Aplicación de Sistemas de Información Geográfica para la elaboración del Mapa Geomorfológico de la Parroquia San Pedro de Vilcabamba, perteneciente al Cantón y Provincia de Loja a escala 1:20 000. - Cevallos Quezada, Leydi Jacqueline (2017)
The present research work entitled "Application of Geographic Information Systems for the elaboration of the Geomorphological Map of the Parish of San Pedro de Vilcabamba, belonging to the Canton and Province of Loja at scale 1:20 000" was designed to identify the geomorphological units of the Parish, through the application of methods based on GIS analysis. For this purpose the geological survey of the parish was carried out in contrast to the application of photogeology. The GIS analysis was based on the determination of morphographic and morphometric indexes, as well as establishing the genesis and age of each of the geomorphological units. The morphography was determined based on the use of the SAGA GIS Software from which the geoforms of the parish were obtained through the methodology established by Iwahashi & Pike, in this analysis we used 3 components: slopes, curvature and terrain texture, giving As a result 8 classes in the automatic mapping of geoforms that are low terrace, alluvial plain, wavy surface, wavy relief, steep relief, low hills, medium hills and mountainous relief. The morphometry was determined through the Arc Gis Software where 3 indexes were used according to those established by Seco; Vertical dissection, slopes and horizontal dissection, resulting in the morphometry of the parish, which was categorized into lumbers and mountains with different slope and dissection variants. Genesis and age were determined based on the previously established geology, 3 types of genesis, depositional, denudatory and erosive tectonic were obtained in addition to the age that varies from the Paleozoic (Chigüinda Unit) to the Quaternary (Alluvial Deposits). Finally the geomorphology of the parish was determined in 12 classes after the contrast of the different maps obtained.